Synthesis of 2,3-dihydronaphtho[2,3-d][1,3]thiazole-4,9-diones and 2,3-dihydroanthra[2,3-d][1,3]thiazole-4,11-diones and novel ring contraction and fusion reaction of 3H-spiro[1,3-thiazole-2,1'-cyclohexanes] into 2,3,4,5-tetrahydro-1H-carbazole-6,11-diones - Konstantinova, Lidia S.; Lysov, Kirill A.; Souvorova, Ljudmila I.; Rakitin, Oleg A. (Beilstein Journal of Organic Chemistry, 2013)
Treatment of N-substituted 2-(methylamino)naphthoquinones 3 and -anthracene-1,4-diones 4 with S2Cl2 and DABCO in chlorobenzene gave the corresponding 2,3-dihydronaphtho[2,3-d][1,3]thiazole-4,9-diones 1 and 2,3-dihydroanthra[2,3-d][1,3]thiazole-4,11-diones 2 by triethylamine addition, in high to moderate yields. The DABCO replacement for N-ethyldiisopropylamine in the reaction of anthracene-1,4-diones 4 led unexpectedly to the corresponding 2-thioxo-2,3-dihydroanthra[2,3-d][1,3]thiazole-4,11-diones 10. The reaction of 3H-spiro[1,3-thiazole-2,1'-cyclohexanes] 1d, 2d with Et3N in chlorobenzene under reflux yielded 2,3,4,5-tetrahydro-1H-carbazole-6,11-diones 15, 16, i.e., ring contraction and fusion products. A plausible mechanism was proposed for the formation of the products.
Keywords: anthracene-1,4-diones; 1H-carbazole-6,11-diones; fused thiazoles; fusion reaction; heterocycles; naphthoquinones; ring contraction; sulfur–nitrogen